Improving the process of dyeing a leather semi-finished product by titanium compounds - Danylkovych, Anatoliy; Lishchuk, Victor; Zhigotsky, Alexander (Eastern-European Journal of Enterprise Technologies, 2016)
We developed technology of dyeing a leather semi-finished product of chrome tanning based on research into the processes of interaction in the system of dermis collagen-azo dye-titanium compounds. Physical and chemical properties of the working solutions of azo dyes, modified by titanium compounds of different chemical composition, were explored. A more energetic interaction was established between the brown azo dye 345, the molecules of which contain phenolic group, and titanium compounds with possible formation of chelate compounds. A study of kinetics of the sorption of azo dyes by collagen fibers, structured by the compounds of chromium, revealed a significant dependence of sorption of the dye, the molecules of which contain less auxochrome –SO3Na-groups, on temperature in the presence of titanyl oxalic acid. In this case, absolute values of the sorption of a dye at temperature of 20 oС are two times lower compared to the brown dye 345. With increasing concentration of the dye with a lower molecular weight, acidic blue-black, modified by ammonium sulfate titanylate, its diffusion capacity into the gel of gelatin is reduced by two times with an increase in the concentration to 80 g/dm3. An increase in the concentration of a dye in the system is symbatic to an increase in the activity of its interaction with collagen, accompanied by reduced diffusion capacity into the gel of gelatin. It was found that filling a semi-finished product of chrome tanning with acrylic polymers contributes to the increase in chemisorption of azo dye when using ammonium sulfate titanylate by 1.5 times. The effect of the composition of dyeing solution on the coloristic properties of a filled semi-finished product was demonstrated when fixating the dye on its surface by ammonium sulfate titanylate. We determined optimal ratio of ammonium sulfate titanylate and a dye, which ensures the formation of leather material with a higher saturation of coloration of the surface of a semi-finished product by 2.1–2.9 %, maximum resistance to wear and light fastness in comparison with the control technology. The designed technology of comprehensive filling-dyeing-greasing makes it possible to reduce the consumption of azo dye, exclude at the final stage of dyeing additional consumption of a dye and environmentally harmful compounds of chromium by the use of ammonium sulfate tytanilate as a fixative of dye with a 5-fold saving of reagent.